Combating Multi-drug Resistant Mycobacterium Species by Efflux Pump Inhibitors: Contemporary Trends - Gautam Kumar; Priya Mondal; Amit Kadam; Isha Dhamija; Ravindra Pal Singh; Deepak Nathiya; Sandeep Kumar (BIO Integration)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis (M.tb) complex (MTBC), which includes M.tb as one of the causative bacteria. In contrast, non-tuberculous mycobacteria (NTM) refers to Mycobacterium spp. that do not cause TB or leprosy (MTBC spp., M . leprae , and M . lepromatosis ). Mycobacterium spp. are responsible for the deadliest infections and remain a significant challenge in diagnosis and treatment. Mycobacterium spp. have developed multiple complementary mechanisms to defend against antibiotics. Specifically, the mechanisms include modifying the drug target sites, enzymatically inactivating the drugs, and lowering intracellular antibiotic concentrations by overexpressing efflux pumps. These adaptations contribute to the emergence of multi-drug resistant pathogens. This review provides an overview of antibiotic resistance in Mycobacterium spp. with a focus on several key factors, such as enzyme-mediated antibiotic deactivation, gene expression, biofilm formation, and the role of efflux pumps. A critical objective of this review includes Mycobacterium efflux pumps, the significant role in antibiotic resistance, and compounds that act against these efflux pumps.